Search for associated production of a Higgs boson and a single top quark in proton-proton collisions at s =13 TeV - Sirunyan, A. M. (2019)
A search is presented for the production of a Higgs boson in association with a single top quark, based on data collected in 2016 by the CMS experiment at the LHC at a center-of-mass energy of 13 TeV, which corresponds to an integrated luminosity of 35.9 fb-1. The production cross section for this process is highly sensitive to the absolute values of the top quark Yukawa coupling, yt; the Higgs boson coupling to vector bosons, gHVV; and, uniquely, their relative sign. Analyses using multilepton signatures, targeting H→WW, H→ττ, and H→ZZ decay modes, and signatures with a single lepton and a bb pair, targeting the H→bb decay, are combined with a reinterpretation of a measurement in the H→γγ channel to constrain yt. For a standard model-like value of gHVV, the data favor positive values of yt and exclude values of yt below about -0.9ytSM.